Homesickness and the Filipino Nation: The Emotional Experience of Propagandists, 1889–1895 - Wani-Obias, Rhodalyn C. (Archīum Ateneo, 2022)
This study focuses on the emotional experience of homesickness of propagandists and relates it to the birthing of the Filipino nation in the late nineteenth century. I show that these young migrant men straddled two worlds, where both modern ideas of individualism and “parochial” sentiments of community existed together. Second, I demonstrate the change in the migrants’ gaze as it slowly began to include the larger entity of the nation. In the end, I argue that these points illustrate tensions found in a nascent nation as Filipinos navigated their emotions within the context of colonialism and modernity.KEYWORDS: MARCELO DEL PILAR • EXILE • HISTORY OF EMOTIONS • NATIONALISM • PROPAGANDA MOVEMENT